Rancang Bangun Mesin Pengaduk Adonan Ampiang - Eko Sulistyo; Eko Yudo (Manutech : Jurnal Teknologi Manufaktur, 2016)
Ampiang or crackers ampiang is typical of Bangka original food made from tapioca, fish, pure water, salt and food flavorings. In the process of making ampiang, there is an obstacle, that is in the process of mixing spices, fish and flour. Mixing or stirring the dough by hand by rotating the dough until the dough is ready to be used takes a long time. To overcome the above problems researchers made kneading ampiang horizontal type with a capacity of 10 kg. The purpose of the research is to get the dough mixing uniformity percentage of 100% and 100% increased production time. The stages of the research are the of collecting data through surveys, questionnaires, interviews, and literature. The next step is data process, manufacture and selection of alternative concept, tool making and assembling, testing and analysis. In making the selection of alternative concepts and decided machine made with size 99 x 66 x 90 cm, using the motor 1PK and design mixer horizontal type. The results show the machine is capable to knead the 10 Kg dough of ampiang in 3 minutes and dough mixing uniformity percentage of 100%.